1998
DOI: 10.1128/iai.66.11.5406-5413.1998
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T-Lymphocyte and Immunoglobulin G2 Responses in Calves Immunized withAnaplasma marginaleOuter Membranes and Protected against Homologous Challenge

Abstract: Protective immunity against the ehrlichial pathogenAnaplasma marginale has been hypothesized to require induction of immunoglobulin G2 (IgG2) antibody against outer membrane protein epitopes and coordinated activation of macrophages for phagocytosis and killing. In the present study, cell-mediated immune responses, including induction of IgG isotype switching, were characterized in calves immunized with purified outer membranes of the Florida strain of A. marginale. Importantly, these calves were subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 49 publications
3
60
0
1
Order By: Relevance
“…Proliferation assays were performed as described previously. 22 PBMC were cultured in replicates of six wells. Concanavalin A (Sigma) was added to positive control wells at ®nal concentrations of 0 .…”
Section: Lymphocyte Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation assays were performed as described previously. 22 PBMC were cultured in replicates of six wells. Concanavalin A (Sigma) was added to positive control wells at ®nal concentrations of 0 .…”
Section: Lymphocyte Proliferation Assaymentioning
confidence: 99%
“…23 Immunoblots Sodium dodecyl sulphate±polyacrylamide gel electrophoresis and immunoblots were performed with mAbs speci®c for bovine IgG1 and IgG2 (Serotec Ltd, Oxford, UK) to determine the subclass of the speci®c IgG response to ovalbumin, as described previously. 22 Antibody complement-mediated depletion assay PBMC were isolated by density gradient centrifugation then resuspended at a concentration of 2r10 7 cells/ml in PBS and incubated for 30 min at 4u with anti-CD4 mAb (IL-A11A; IgG2a) diluted to a ®nal concentration of 15 mg of mAb per ml. Cells were washed twice with PBS, then re-suspended in PBS and incubated for 30 min at 37u with an equal volume of a 1 : 8 ®nal dilution of rabbit complement (Pel-Freez Clinical Systems, LLC., Brown Deer, WI).…”
Section: Lymphocyte Proliferation Assaymentioning
confidence: 99%
“…While the MSP5 cELISA assay is very useful for measuring seroconversion as an indicator of infection, it has limited application in estimating protective immunity. Measuring the IgG response against all MSPs, either by ELISA as used here, or by Western blot as in Brown et al (1998), appears to give more information on the likely degree of cross-protection induced by infection or vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of activated macrophages and high levels of IgG2 would lead to increased opsonization and phagocytosis of the rickettsia. To corroborate this, Brown et al (1998) found that protection after vaccination with outer membranes was associated with CD4+ proliferation and IFNc production and high IgG2 levels. Anaplasma marginale infection itself leads to the down-regulation of high pre-challenge, vaccinationinduced, CD4 T-cell responses.…”
Section: Introductionmentioning
confidence: 91%
“…CD4+ T-cells should contribute to protection against CBPP mainly through their cytokine network including IFNg that will enhance phagocytosis and cell killing ability and promote the expression of MHC class II molecules, thus increasing the host cell capacity for antigen processing and epitope presentation to T-lymphocytes [14]. A protective role for the IFNginduced IgG2 antibody, only able to promote killing by neutrophils in cattle, is also expected since neutrophil recruitment has been observed in CBPP lung lesions [15][16][17]. Besides, CD4+ T-cells play also a key role in facilitating B-cell proliferation and class-switching to give rise to antigen-specific IgAs in mucosal effector sites [5].…”
Section: Protective Immune Parametersmentioning
confidence: 99%